Receipts for cable transfers, 1941 - Chase National Bank of the City of New York (1941)
Receipts for cable transfers belonging to Max Bredig (1902-1977) who had wired money to his family in Europe.
Keywords: Jewish Holocaust (1939-1945); Chase National Bank of the City of New York; Bredig, Max Albert, 1902-1977